Strategic Planning in Hungarian Municipalities - Izabella BARATI-STEC (Transylvanian Review of Administrative Sciences, 2015)
The paper gives a summary of the most recent literature on strategic planning in local governments, while placing the fi ndings in a historical context. It focuses on planning in postsocialist countries, the impact of the heritage of decades of central planning and the relationship between decentralization and planning. The study concludes that while strategic planning improves the performance of local governments, special aspects, such as the fi nancial dependency of municipalities, focus on daily operation and on short-term results and enhanced need of institutional and personal capacity management must be taken care of while implementing strategic planning in local governments.